Bactericidal activity of essential oil of oregano ( origanum spp.) Grade and blood (croton lechleri) compared with chlorhex1dine gluconate 0.12% and 0.2% porphyromonas gingivalis on - Ruth Alvarez Monge (2019)
Porphyromonas Gingivalis is a pathogen of great importance in odontogenic infections, periodontitis is a disease difficult to treat because of resistance to antibiotics commonly used in the field of periodontics. It is important to look for new therapeutic alternatives, including the use of natural products with antibacterial properties. The present study is an in vitro laboratory research aimed to assess the bactericidal activity of essential oil Origanurn spp. (Oregano) and Croton lechleri (Dragon’s Blood) on periodontal pathogenic bacteria Porphyromonas gingivalis, compared with chlorhexidine gluconate, a product commonly used in periodontics, in solution at 0.12 and 0.2%.We determined the MIC of the essential oil of Origanum spp. (6.25%) and MBC (12.5%).Results were compared with chlorhexidine hydrochloride solution 0.12% and 0.2%. The results showed that the essential oil of Origanum spp. And Croton lechleri have bacteriostatic and bactericidal activity against Porphyromonas gingivalis and showed that both the essential oil of oregano to 12.5% and blood 30% grade have better bactericidal activity against chlorhexidine gluconate 0.12 and 0.2%